Application of Online Learning Methods in Indonesian Language Subjects at SD Nurul Falah Sibolga Case Study Class V - Yusi Tri Utari Panggabean (PT Inovasi Pratama Internasional, 2022)
This research is motivated by the low learning outcomes of the fifth grade Indonesian students of SD Nurul Falah. This is 40% of students with perfect criteria, as you can see from the daily test results of students with 60% incomplete criteria. These results reveal that the fifth grade students of SD Nurul Falah still have low learning success, especially in Indonesian subjects. Educators play a key role in determining student learning outcomes. Observations show that due to the current learning of the WhatsApp application, some students have poor learning outcomes, do not have mobile phones, some are lagging behind in learning, and others do not understand much. I don't understand the dated material sent by the educator via WhatsApp. This research is a qualitative field research that aims to explain the application of online learning methods in Indonesian class V subjects at Nurul Falah Elementary School in the 2021 academic year. The learning method here uses the whatsapp grub application, the subject of this research is class V students, totaling 20 students. Data collection techniques used are observation, interviews, and documentation. the online learning method for Indonesian subjects in class V is successful. This is evidenced by educators who motivate their students and their parents as their study partners. Exit activity in WhatsApp group. B. Publish the researched material and provide a description of the assignment assignment material collected.